WAYS OF IMPLEMENTATION OF AUTHOR'S EXPERIENCE SCHOOLS IN PROFESSIONAL TRAINING MUSIC TEACHER - T.Y. Reyzenkind (Academy of Cognitive and Natural Sciences, 2022)
In article the structure of semantic model of vocational I mining o f the teacher o f music is considered. The system of interactions o f components o f structure on a polyphonic basis is analyzed. Such spheres of polyphonic structure, as formation integration knowledge, poly-art skills, complex feelings, personal senses come to light.